2018
DOI: 10.1037/pne0000115
|View full text |Cite
|
Sign up to set email alerts
|

Gestures and related skills in developmental coordination disorder: A production-system deficit?

Abstract: The present study investigated the nature and specificity of the gestural deficit in children with developmental coordination disorder (DCD). Performance of children with DCD is compared with that of typically developing children across tasks and conditions that allow exploring distinct levels hypothesized by adult models of praxis processing. These models generally involve a conceptual system and a production system. Within this theoretical framework, the study analyzed the extent to which the gestural diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
(135 reference statements)
0
4
0
Order By: Relevance
“…There were 14 studies (13 high quality and 1 low) that contributed effect sizes in the sensori-perceptual task category, the magnitude of which was large overall ( d = 0.86, 95% CI [0.48, 1.25]), but with substantial heterogeneity ( I 2 = 87.2%) (Ghotbi et al, 2016 ; Prunty et al, 2016 ; Johnston et al, 2017 ; Wang et al, 2017 ; Costini et al, 2018 ; de Waal et al, 2018 ; Tseng et al, 2018 , 2019a , b ; Alesi et al, 2019a ; Chen et al, 2019 , 2020 ; Adi-Japha and Brestel, 2020 ; Nobusako et al, 2021 ). The combined ESs are presented in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 14 studies (13 high quality and 1 low) that contributed effect sizes in the sensori-perceptual task category, the magnitude of which was large overall ( d = 0.86, 95% CI [0.48, 1.25]), but with substantial heterogeneity ( I 2 = 87.2%) (Ghotbi et al, 2016 ; Prunty et al, 2016 ; Johnston et al, 2017 ; Wang et al, 2017 ; Costini et al, 2018 ; de Waal et al, 2018 ; Tseng et al, 2018 , 2019a , b ; Alesi et al, 2019a ; Chen et al, 2019 , 2020 ; Adi-Japha and Brestel, 2020 ; Nobusako et al, 2021 ). The combined ESs are presented in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…There were 21 studies (15 high quality, 4 moderate, and 2 low) that assessed aspects of executive function and intelligence, with a moderate overall effect ( d = 0.49, 95% CI [0.40, 0.59]) (Rahimi-Golkhandan et al, 2016 ; Schott et al, 2016 ; Sumner et al, 2016 ; Adams et al, 2017b ; Johnston et al, 2017 ; Mirabella et al, 2017 ; Wang et al, 2017 ; Bernardi et al, 2018 ; Costini et al, 2018 ; He et al, 2018a ; Koch et al, 2018 ; Michel et al, 2018 ; Thornton et al, 2018 ; Alesi et al, 2019b ; Barbacena et al, 2019 ; Job et al, 2019 ; Adi-Japha and Brestel, 2020 ; Gomez-Moya et al, 2020 ; Sartori et al, 2020 ; Suzuki et al, 2020 ; Wilson et al, 2020 ). The combined ESs are presented in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subara-Zukic and colleagues found that children with DCD have deficits in visual–motor mapping and cognitive–motor integration, manifested in the abnormal maturation of motor networks, and an area of practical compensation for motor control deficits ( Subara-Zukic et al, 2022 ). So the relationship between cognitive functions and motor control has also been highlighted in DCD ( Costini et al, 2018 ). Some studies have also suggested that abnormal brain motor imagery is an important factor leading to the impairment of motor activity in DCD ( Barhoun et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%